2006
DOI: 10.1016/j.matdes.2004.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Predicting energy absorption in a foam-filled thin-walled aluminum tube based on experimentally determined strengthening coefficient

Abstract: The energy absorption in a foam-filled thin-walled circular Al tube was investigated based on the experimentally determined strengthening coefficient of filling using Al and polystyrene closed-cell foams with three different densities. Foam filling was found to change the deformation mode of tube from diamond (empty tube) into concertina, regardless the foam type and density used. Although foam filling resulted in higher energy absorption than the sum of the energy absorptions of the tube alone and foam alone,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(62 citation statements)
references
References 15 publications
2
59
0
1
Order By: Relevance
“…As is shown in Fig. 17, empty box is energetically more efficient than fully and partially foam filled boxes until about a critical foam relative density, agreeing with the previous studies [16,24]. The critical foam density for efficient foam filling increases slightly as the box wall thickness increases in fully foam filled boxes.…”
Section: Resultssupporting
confidence: 89%
“…As is shown in Fig. 17, empty box is energetically more efficient than fully and partially foam filled boxes until about a critical foam relative density, agreeing with the previous studies [16,24]. The critical foam density for efficient foam filling increases slightly as the box wall thickness increases in fully foam filled boxes.…”
Section: Resultssupporting
confidence: 89%
“…This effect, the increase in SAE values of filled tubes over the empty tube at increasing displacements, is simply a result of the increase of the foam filler density at increasing deformation ratios. It was previously shown that there is a critical total tube mass and the corresponding critical foam density above which the use of foam filling becomes more efficient than empty tube [1,2]. The SAE values of empty multi-tube designs however exceed that of the single empty tube after 10 mm displacement as shown in Figures.…”
Section: Analysis Of the Resultsmentioning
confidence: 84%
“…In empty hybrid tubes, although metal tube crushes in inhomogeneous diamond mode, it deforms in concertina mode in the foam-filled hybrid tube. The concertina folds in a foam-filled Al tube were previously shown to be uniform in shape and thickness and mostly outward of the filler [2]. While in hybrid tubes the folds are not as regular as in the case of foam-filled Al tube and tend to form through the inside of the foam.…”
Section: Materials and Testing Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…In recent years, tubular structures, specifically circular and square tubes under axial compression, have been explored by diversified experimental, theoretical and numerical means [1][2][3][4][5]. Not only circular and square tubes, numerous but also other cross-sectional tubes have also become the aim of research, including hexagonal tubes, octagonal tubes, 12-side star tubes, 16-side star tube s(also known as even side tubes) [6][7][8][9][10][11][12], as well as triangular tubes and pentagonal tubes (also known as odd side tubes) [13][14][15].…”
Section: Introductionmentioning
confidence: 99%